(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The influence of digital videos on our everyday culture is undeniable. Online video-sharing sites such as YouTube, Vimeo, and Metacafe boast monthly audience numbers in the millions. With digital videos gaining popularity, it seems natural that this familiar and widespread platform should extend into the education system. Today’s Students are using educational videos to learn everything, from basic skills - like changing a tire - to the latest dance craze. Remarkably, millennials make up 92% of the digital video-viewing audience. Abstract topics that once seemed difficult to teach and learn are now more accessible and understandable, thanks to the availability of effective educational video platforms for online learning. Studies have shown that short video clips allow more efficient processing and memory recall. The visual and auditory nature of videos appeals to a wide audience and allows users to process information naturally.